Music's Multilayered Subversion of the Word - Heaney, Maeve Louise 1967-; Hillman, Roger 1946- (2017)
This article explores the polyvalent nature of musical meaning and its contribution to theological reflection in a hermeneutical key, from the perspective of two composers in dialogue about their music. Against an analytical theoretical backdrop drawn from both musicology and theology-Jean-Jacques Nattiez's semiological tripartition method and Bernard Lonergan's understanding of consciousness and intentional analysis-the article explores various aspects of the relationship between words and music from a theological perspective. The aim is to present and exemplify music's contribution to the resonance and complexity of words and thought in theological discourse.